Research progress of Traditional Chinese Medicine treatment and nursing interventions after hip fracture surgery (髋部骨折术后中医疗法的应用研究进展) - ZHONG Lin (钟琳); HUANG Yi (黄旖); YU Yuxiu (于玉秀) (中西医结合护理)
Postoperative swelling and pain of hip fracture will affect the early recovery of limb function, and then produce complications, which will have a certain impact on the future life of patients. This article describes the clinical application of Traditional Chinese Medicine (TCM)treatment and nursing methods such as TCM oral administration, TCM external treatment, diet regulation and emotional guidance in alleviating postoperative swelling and pain of hip fracture, with a view to providing new ideas for the related research on reducing postoperative swelling and pain after hip fracture surgery. (髋部骨折术后肿痛会影响患者肢体功能早期康复, 降低生活质量。本文阐述中药内服、中医外治、饮食调护、情志疏导等中医疗法在减轻髋部骨折术后肿胀、疼痛的临床应用现状, 以期为制定预防或减轻髋部骨折术后肿胀、疼痛的相关干预措施提供新的思路。)